2022
DOI: 10.1038/s12276-022-00795-z
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of the RNA m6A reader signature is associated with poor survival by enhancing cell proliferation and EMT across cancer types

Abstract: N6-Methyladenosine (m6A) RNA modification plays a critical role in the posttranscriptional regulation of gene expression. Alterations in cellular m6A levels and m6A-related genes have been reported in many cancers, but whether they play oncogenic or tumor-suppressive roles is inconsistent across cancer types. We investigated common features of alterations in m6A modification and m6A-related genes during carcinogenesis by analyzing transcriptome data of 11 solid tumors from The Cancer Genome Atlas database and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
3
0
Order By: Relevance
“…Many cancers exhibit alterations in the expression of m6A-related genes and cellular m6A levels. However, the oncogenic or tumour-suppressor roles of m6A are inconsistent across cancer types [ 8 ], and the role of m6A in EOC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Many cancers exhibit alterations in the expression of m6A-related genes and cellular m6A levels. However, the oncogenic or tumour-suppressor roles of m6A are inconsistent across cancer types [ 8 ], and the role of m6A in EOC remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…M6A clusters with increased expression of IGF2BPs showed the worst outcomes in STAD and ESCA. Indeed, previous studies have showed that the reader and especially the IGF2BPs were upregulated in cancers, patients with a high IGF2BPs signature exhibited poor prognosis across cancer types [ [29] , [30] , [31] ]. However, the clusters in COAD and READ characterized by nearly all m6A regulators with reduced expression showed the best results in the survival analysis.…”
Section: Discussionmentioning
confidence: 99%
“…ROC analysis revealed an area under the curve of 0.929, outperforming commonly used biomarkers such as carcinoembryonic antigen and carbohydrate antigen 199. This indicated that the m6A levels in peripheral blood RNA have high accuracy in diagnosing gastric cancer [ 169 , 170 ]. In pancreatic cancer, m6A levels showed promise as a predictive and prognostic marker.…”
Section: M6a Modification As Diagnostic and Prognostic Indicators In ...mentioning
confidence: 99%